O espaço da biblioteca escolar: dinamização do acervo do PNBE 2013 nos anos finais do ensino fundamental - Vargas, Thiane de (2016)
In the educational context, the library and its actors are important protagonists in the students social construction due to educative and cultural possibilities they may provide through the enhancement of their collection and teaching action. This investigation - namely the school library as a space for readers formation - proposes a study considering the enhancement of the literature collection from Programa Nacional Biblioteca na Escola (PNDE) National Program Library in Schools - of 2013, through the active participation of teachers in the library space of a public school which is part of the municipality of Passo Fundo-RS. The PNDE is part of a governmental policy for encouraging new readers promoted by the federal state, which historically attempts at securing the access of public school students to quality literature. Aware of the importance of PNDE in schools, the dimension school libraries have in the process of forming readers, and the reality of how this space has been treated, the importance of researching ways of enhancing the literature collection from PNDE located in libraries is understandable. In this sense, the general aim of such investigation is to (re)signify the use of space and the reading mediation through the enhancement of the literature collection of the 2013 PNDE, targeting the formation of new critical readers who may contribute to society. The study is directed at students in their final years of elementary school. It is a bibliographical and exploratory work whose procedures may be considered as those from an action research. The theoretical corpus by Chartier (1999, 2002, 2007, 2010, 2014, 2016), Silva (1986, 1996, 2009), Zilbermann (2009) is used to discuss the reading matters as well as the reader formation. Lévy (1999) points to questions of cyberspace, cyber culture, and the variety of reading resources available to readers. Cool (2010) discusses the relevance of information technologies and communication in education. Still, it must be pointed out the protagonism of the new reader profiles debated by Santaella (2204, 2013). Finally, Rosing (1996, 2001, 2009, 2011), Santos (2009) e Silva (2009) contribute with their view concerning the teacher and it role as a reading mediator in school libraries. So as to reflect on Programa Nacional Biblioteca na Escola, official documentation on the Policies of Reading Formation and in Ramos (2013) are used. The activity proposal in the library space happened through the construction of a set of portfolios aiming at enhancing the PNDE 2013 literature collection, with the collaboration of the teacher responsible for the library and the organization of such space as a cultural multimedia center. This initiative contributes to awaken the students interest for the literary reading and consequently for the enhancing of their cultural sphere